Hybrid rice collection (International Rice Research Institute, 1986)
This collection contains the proceedings of the four previous International Hybrid Rice Symposia, plus the Two-Line Hybrid Rice Breeding Manual and the terminal report of the Develop-ment of Hybrid Rice Technology.